Penyusunan Tes Penalaran Abstrak - Chandra, M. Tri Firia; Rendita, Bella Fanya; Syafitri, Astika; Friscilya, Anggita; Weri, Firda; Afriana, Nur; Slamet, Edi; Periantalo, Jelpa (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2017)
INTRODUCTION Abstract reasoning refers to the ability to analyze information, detect patterns and relationships, and solve problems on a complex, intangible level. Based on Piaget’s theory, it is said that abstract reasoning has started at age of 11 years old and above. METHOD This scale based on construction methods of measuring instruments. This research included 600 respondents overall from age 13 to 35 years old. There were 100 items that divided into five indicators. The item analysis was done by the item discrimination index, item difficulty index, the effectiveness of the distractor, validity views of content validity, convergent validity, discriminant validity, groups validity,criterion validity, and reliability analysis. Norms are made by using score-standard or z-scores method. RESULTTheresult of convergent validity between the Abstract Reasoning Test’s components is a positive correlation. Discriminatory with r = 0,078 and Sig. = 0,271 shows that there was not much difference of abstract reasoning ability between women and men. There was a significant correlation between education and abstract reasoning ability with r = 0,405 and Sig. = 0,000, and there was also a significant correlation between age and abstract reasoning ability with r = 0,472 and Sig. = 405. Internal consistency reliability using the SPSS output coefficient of reliability of 0,809, and it shows the Abstract Reasoning Scale has a good reliability scores. CONCLUSION DAN RECOMMENDATION The instrument has good psychometric properties. It has good results on validity tests and standards-compliant reliability. The instrument is also practically used. Final scale consists of 25 items. Abstract reasoning ability is proven to be correlated with education and age. The higher one’s education, the higher abstract reasoning ability will be. Also the older one gets, the more abstract reasoning ability one will possess.